Case Report: Effect of preventive intravenous iron infusion on postoperative hemoglobin levels in a female patient with latent iron deficiency anemia before total hip arthroplasty - Zhanarystan, Nazerke; Shayakhanov, Shamil; Konkayeva, Maiya; Kadralinova, Assiya; Konkayev, Aidos (Frontiers in Medicine, 2025)
This article presents a case of orthopedic treatment of a 51-year-old patient with latent iron deficiency anaemia and congenital dysplasia of both hip joints. The patient was admitted with complaints of severe pain and restriction of movement in the right hip joint, impaired joint function, shortening of the right lower limb, and lameness. A year prior, the patient had undergone surgery on the left hip joint to treat the same complaints. During the left hip surgery, the patient required haemotransfusion in the postoperative period to manage severe posthemorrhagic anaemia. In this clinical case, under equal conditions, the patient underwent preoperative preparation and administration of ferric carboxymaltose to compare the efficacy of iron deficiency correction versus no correction. No haemotransfusion was required in the postoperative period. The uniqueness of this clinical case is represented by the fact that the example of one patient showed the importance of preparation for orthopedic intervention and iron deficiency correction to avoid haemotransfusions, which are closely associated with infectious complications. In conclusion, preoperative correction of iron deficiency and treatment of latent anaemia in this clinical case was associated with no need for haemotransfusion in the postoperative period compared to no preoperative preparation. Further studies are needed.